2018
DOI: 10.1093/hropen/hoy013
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and blood pressure in 6-year-old singletons born after pre-implantation genetic testing for monogenic and structural chromosomal aberrations: a matched cohort study

Abstract: STUDY QUESTION Does Day 3 embryo biopsy for pre-implantation genetic testing for monogenic (PGT-M) and structural chromosomal aberrations (PGT-SR) affect body composition and blood pressure readings of 6-year-old singletons? SUMMARY ANSWER This study of 87 PGT-M and PGT-SR conceived singletons showed no differences in anthropometric measurements and blood pressure readings in comparison with a matched cohort of peers born after ICSI without embryo biopsy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…aged children born after IVF/ICSI and naturally conceived children from families with a genetic disorder. A study of 6-year-old children born after PGD showed no difference in BMI when compared with children born after ICSI (9). However, an earlier study of the same research group of 2year-old children born after PGD and PGS found that they had slightly lower BMIs than children born after NC (8).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…aged children born after IVF/ICSI and naturally conceived children from families with a genetic disorder. A study of 6-year-old children born after PGD showed no difference in BMI when compared with children born after ICSI (9). However, an earlier study of the same research group of 2year-old children born after PGD and PGS found that they had slightly lower BMIs than children born after NC (8).…”
Section: Discussionmentioning
confidence: 90%
“…Desmyttere et al (7,8) studied health and auxological data (outcome measures: weight, height, head, arm, and waist circumference) of 2-year-old children born after PGD or preimplantation genetic screening (PGS). Some of these children were also studied at the age of 6 and compared with children born after ICSI (9). Banerjee et al (10) reported on the health, height, and weight of 10 children born after PGD with a mean age of 18.4 months.…”
mentioning
confidence: 99%
“…There are no previous studies published investigating the early childhood outcome for PGT children concerning somatic and psychiatric diseases. The few earlier studies on growth, neurological development, body composition and blood pressure (Desmyttere et al, 2009, Belva et al, 2018, Kuiper et al, 2018 all suffer from small sample sizes and methodological problems such as unclear selection of controls, data reported by questionnaires to the parents and low participation rates.…”
Section: Commentsmentioning
confidence: 99%
“…Developmental neurological and cognitive assessment and follow-up on psychomotor and social functioning showed that PGT pre-schoolers were comparable with controls born after ICSI or after spontaneous conception (Winter et al 2014, Sacks et al 2016, Heijligers et al 2019. Another study on body composition and blood pressure showed no adverse outcomes for 6-year-old children born after PGT (with day 3 embryo biopsy followed by blastocyst transfer) compared to children born after ICSI without embryo biopsy (Belva et al 2018). In summary, the follow-up results have so far been reassuring but further monitoring of the safety of PGT and the long-term health of the children remains necessary.…”
Section: Children Follow-upmentioning
confidence: 97%